Making Learning Fun - Keith G. Diem; Judy Levings (EDIS, 2014)
As a 4-H volunteer, one of your most important roles is helping youth learn. Especially because membership in 4-H is voluntary, learning in 4-H must be fun. Even if you’re not a teacher by profession, you can successfully guide youth to learn communication, leadership, citizenship, and other life skills, as well as subject matter through their 4-H projects and club participation. This 5-page fact sheet was written by Keith G. Diem and Judy Levings, and published by the UF Department of 4-H Youth Development, July 2014.